Impact of COVID-19 pandemic on the utilization of ART Centre Services of a teaching hospital - Bhujade, Rashmi; Srivastva, Anupama; Agrawal, Renu; Baghel, Anil (Indian Journal of Community Health, 2024)
Background- COVID-19 pandemic has had a huge impact on the collateral health system. It made access to essential health services difficult. Such an essential service is a service provided to HIV patients. This study was planned to assess the effect of the current COVID-19 pandemic on Anti-Retroviral therapy (ART) center services. Methods -Pre-recorded epidemiological data from an ART center of a teaching hospital was used to answer the research question. Data was collected for retrieving 4 parameters i.e. number of registrations, number of HIV-positive patients kept on ART, number of deaths, and loss to follow up of the COVID-19 year and non-COVID-19 year then comparison was made between both. Data analysis was done with the help of SPSS. Independent t-test, one-way ANOVA test, and multiple comparison Tuckey’s test were applied. Results- Statistically significant difference was noted in the total number of registrations, the number of patients kept on ART, death, and loss to follow-up in non- COVID-19 & COVID-19 years. After appling above mentioned statistical test the p-value came out to be <0.05. Conclusion-COVID-19 pandemic has adversely affected the auxiliary non-COVID-19 health services and health programs. The current study gives evidence that ART functioning is negatively affected by the COVID-19 pandemic.